Differential Functional Connectivity in Anterior and Posterior Hippocampus Supporting the Development of Memory Formation - Tang, Lingfei; Pruitt, Patrick J.; Yu, Qijing; Homayouni, Roya; Daugherty, Ana M.; Damoiseaux, Jessica S.; Ofen, Noa (Frontiers in Human Neuroscience, 2020)
Neuroimaging evidence suggests that the development of the hippocampus, a brain structure critical for memory function, contributes to the improvements of episodic memory between middle childhood to adulthood. However, investigations on age differences in hippocampal activation and functional connectivity and their contributions to the development of memory have yielded mixed results. Given the known structural and functional heterogeneity along the long axis of the hippocampus, we investigated age differences in the activation and functional connectivity in hippocampal subregions with a cross-sectional sample of 96 participants ages 8 to 25 years. We found that anterior and posterior hippocampus supported memory formation, and there was an overall stability in memory-related hippocampal activation with age. Without taking account of memory outcome, direct contrast between subregions showed higher functional connectivity of anterior, compared to posterior hippocampus, with regions in the inferior frontal and lateral temporal lobes, and higher functional connectivity of posterior, compared to anterior hippocampus, with regions in the medial and superior frontal, inferior parietal, and occipital lobes. A direct contrast between the memory-related connectivity patterns of anterior and posterior hippocampus identified a region in the medial frontal cortex, with which anterior and posterior hippocampus were differentially functionally connected. Finally, we identified age differences in memory-related differential hippocampal functional connectivity with several frontal and visual/sensory cortices, underscoring the importance of examining age differences in the patterns of hippocampal connectivity. Moreover, the specific patterns of differential anterior and posterior functional connectivity indicate an increase in the functional specialization along the long axis of the hippocampus and a dynamic shift in hippocampal connectivity patterns that supports memory development.